Determinants of Purchase Decisions for Imported Packaged Food among Muslim Consumers in Kudus Regency - Maula Dwi Nastrilia; Agung Slamet Sukardi (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This research explores the upward trend in the consumption of imported packaged foods, many of which lack halal certification, alongside the higher costs associated with these imports compared to local alternatives. This situation complicates the ability of Muslim consumers in Kudus Regency to ascertain halal status and make purchases that align with their financial capabilities. This study is conducted to analyze the impact of the impact of religiosity, halal awareness, and income on the purchase decisions of imported packaged food products among Muslim consumers in Kudus Regency, both individually and collectively. The employed methodology is an explanatory quantitative technique, in which data from 100 respondents selected through purposive sampling were then analyzed using SPSS. The study demonstrates that all independent variables contribute positively and significantly to purchase decisions, both on their own and in combination, accounting for 69.9% of the dependent variable, with the remaining portion explained by factors beyond the scope of this research. This study indicates that religiosity, halal awareness, and income are significant determinants in the purchase decisions of Muslim customers for imported packaged food in Kudus Regency. Therefore, all three should be incorporated into marketing plans and halal product regulation policies.